Iran's troubled modernity : debating Ahmad Fardid's legacy - Mirsepassi, Ali (New York : Cambridge University Press, 2019)
This book continues my earlier study on the influence of the Heideggerian counter-Enlightenment in Iran. My last book,'Transnationalism in Iranian Political Thought,' focused on Ahmad Fardid's thought, as part of the broader circulation of intellectual ideas to Iran (European counter-Enlightenment tradition), and the reception of Persian Islam to Europe (in Henry Corban's thought). The book explores the nature of these ideas and tradition as they travel back and forth. More specifically, I examined the ideological hazards of excessive anti-modernity, projected in the Gharbzadegi discourse (Westoxification) in Iran. I further discussed the social significance of politicized Erfan (Persian mysticism), or the desire for achieving'Eastern Spirituality', and the violently anti-democratic predicament of what Michel Foucault celebrated as the'politics of Spirituality.' The current volume continues this important scholarly investigation, although in a rather different format. This new and complimentary book engages in a dialogue on Ahmad Fardid's intellectual legacy, by those who admire him, some who were once inspired by him but are now critical of his thinking, and others who may hold a more mixed and ambivalent view of Fardid and his ideas.
Ahmad Fardid and his legacies -- Introduction -- Fardid's life -- The man and his life -- Conversations on Fardid's life and thought: -- Hossein Nasr : for Fardid, Corbin was worthless, but, the Shah was great -- Daryush Ashuri : Fardid was not very religious -- Ramin Jahanbeglu : Fardid was at the center of Fardiddiyeh (Fardid and Fardiddiyeh) -- Abbas Amanat : Fardid whom I came to know -- Ali Reza Meybodi : Fardid was'Dante's inferno' -- Behrouz Farnou : Fardid's thought was post-modern -- Ehsan Shari'at i: Fardid misunderstood Heidegger -- Seyyed Ali Mirfattah :'I admired his anti-capitalism and his anti-Americanism' -- Mohammad Reza Jozi : Fardid's philosophy was not political -- Mansour Hashemi : Fardid pioneered post-Bergson philosophy in Iran -- Ata'ollah Mohajerani : philosophers need power -- Seyyed Javad Mousavi : Fardid was a great man, with many failings -- Abdolkarim Soroush : Fardid did not impress me at all -- Biographies -- Glossary -- Bibliography.
Includes bibliographical references and index.
Keywords: Fardid, Ahmad, -- 1910 or 1911-1993 or 1994.; Philosophy -- Iran -- History -- 20th century; Islam and politics -- Iran -- History -- 20th century; Mysticism -- Political aspects -- Iran; East and West